2007
DOI: 10.1002/adsc.200600400
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Approach to Unsymmetric Atropoisomeric Bipyridine N,N′‐Dioxides and Their Application in Enantioselective Allylation of Aldehydes

Abstract: The [2 + 2 + 2] cyclotrimerization of 1-isoquinolinyl-1,7-octadiyne with benzonitrile catalyzed by CpCo(CO) 2 opened a new pathway for a synthesis of unsymmetrical axially chiral bipyridine N,N'-dioxides. The N,N'-dioxide 3a was found to be highly catalytically active and enantioselective for the asymmetric allylation of aldehydes with allyltrichlorosilane. The allylation took place with even 1 % of the catalyst with an enantioselectivity up to 87 % ee.Keywords: allylation; asymmetric catalysis; Lewis bases; m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(27 citation statements)
references
References 38 publications
3
23
0
1
Order By: Relevance
“…Moreover in all the non-coordinating solvents the predominant enantiomer of the product had opposite configuration (as also observed in Ref. [38][39][40][41][42]) as compared with O-coordinating solvents. Dichloromethane was found to be the most appropriate solvent: the absolute values of enantiomeric excess reached 37% ee.…”
Section: Resultsmentioning
confidence: 59%
“…Moreover in all the non-coordinating solvents the predominant enantiomer of the product had opposite configuration (as also observed in Ref. [38][39][40][41][42]) as compared with O-coordinating solvents. Dichloromethane was found to be the most appropriate solvent: the absolute values of enantiomeric excess reached 37% ee.…”
Section: Resultsmentioning
confidence: 59%
“…Benzofuro-and benzothienopyridines are the primary molecular architectures of many biologically active compounds and drug candidates, [22] and find application in materials science as well. [23] Theversatility of this method was furthered by setting up new approaches to isoquinolines (product 21 a), 2-(isoquinolin-1-yl)quinolones (product 21 b), [24] and 4-hydroxyisoquinolines (product 21 c), which otherwise require multistep synthesis.Isoquinolines are the key structural scaffolds of several naturally occurring alkaloids;t hey are also the principal components of numerous therapeutics and can provide the backbone for chiral ligands. [25] In conclusion, we have presented unprecedented examples of relay catalysis through the sequential use of silver, bismuth, and palladium catalysts to access an array of distinct b-carbolines.T he method was subsequently extended to the synthesis of intriguing [c]-fused pyridines,such as benzofuroand benzothieno [2,3-c]pyridines,a nd isoquinolines.I ntriguing mechanistic details governing these processes were elucidated.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…16,17 The experiments were performed with a TSQ Classic mass spectrometer equipped with an electrospray ion source and a QOQ configuration of the manifold (Q stands for quadrupole and O for octopole). Mixing milimolar amounts of catalysts with reference bases -DIPEA (diisopropylamine), TPA (tripropylamine), TBA (tributylamine), TEA (triethylamine) and DMAN (N,N,N′,N′-Tetramethyl-1,8-naphthalenediamine) in methanol (HPLC quality) lead to the formation of mixed proton-bound complexes of the structure [A-H-B] + where A stands for the catalyst and B for the reference base.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown previously that catalysts derived from the axially chiral 2,2′-bipyridyl N,N′-dioxide or 2-aryl pyridine N-oxide are very efficient as catalysts of the reaction shown in Scheme 1 providing both high yields and high enantioselectivities. [16][17][18][19][20] By combination of an extended kinetic method and theoretical calculations we aimed at determining the gas-phase proton affinities of a series of organocatalysts employed in the allylation reaction (Chart 1) and theoretical values of their acidity constants in solution (pK a ). Recently, we have shown that molecules derived from 2,2′-bipyridyl N,N′-dioxide have very large proton affinities (1050 -1070 kJ mol -1 ) in the gas phase and can be denoted as superbases.…”
Section: Introductionmentioning
confidence: 99%